2010
DOI: 10.1080/14639220903009953
|View full text |Cite
|
Sign up to set email alerts
|

Is it really better to share? Distributed situation awareness and its implications for collaborative system design

Abstract: Despite well over two decades of academic research, situation awareness in complex collaborative environments remains ambiguous. Recent systems-based models of distributed situation awareness have attempted to address this; however, further effort is required in clarifying exactly how situation awareness operates in complex socio-technical systems. One pertinent issue regards what the 'distributed' situational picture looks like from the perspective of each component of the system and how it differs amongst te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…In highly dynamic, complex, uncertain, and risky environments, the role of situation awareness becomes pivotal. This has been seen in studies of commercial aviation (Sarter & Woods, 1992), anesthesiology (Gaba et al, 1995) and firefighting (Jiang et al, 2004), where collaborators are able to see or hear the same information, but they understand it differently (Heath & Luff, 1992;Dourish & Bellotti, 1992;Endsley et al, 2003;Salmon et al, 2010). For instance, Sarter & Woods (1992) explored the interactions between pilots and the Flight Management System (comprised of electronic flight instrument displays).…”
Section: Shared Situation Awarenessmentioning
confidence: 99%
“…In highly dynamic, complex, uncertain, and risky environments, the role of situation awareness becomes pivotal. This has been seen in studies of commercial aviation (Sarter & Woods, 1992), anesthesiology (Gaba et al, 1995) and firefighting (Jiang et al, 2004), where collaborators are able to see or hear the same information, but they understand it differently (Heath & Luff, 1992;Dourish & Bellotti, 1992;Endsley et al, 2003;Salmon et al, 2010). For instance, Sarter & Woods (1992) explored the interactions between pilots and the Flight Management System (comprised of electronic flight instrument displays).…”
Section: Shared Situation Awarenessmentioning
confidence: 99%
“…Compatible awareness is therefore the phenomenon that holds distributed systems together (Salmon et al, 2009). The first effort to use the DSA in improving process safety has been conducted by Nazir et al (2014c).…”
Section: Situation Awareness and Process Industrymentioning
confidence: 99%
“…Salmon et al (2010) suggested that the SA is maintained in the system by the exchange of information between the agents or the transactions of SA. Teams with more transactions between members are found to perform better than teams with less transactions (Sorensen & Stanton, 2016).…”
Section: Distributed Situation Awarenessmentioning
confidence: 99%
“…Notably the notion that SA at team level is compatible in nature. Salmon et al (2010) theorize that the different team members due difference in goals, roles, schemas etc.…”
Section: Distributed Situation Awarenessmentioning
confidence: 99%